Availability and Utilization of E-Learning Technology Resources in Teaching Business Education Subjects - Abdulrazak , Mohammed; Adeoye, Moses Adeleke (Universitas Negeri Semarang, 2024)
The study explores the availability and utilisation of e-learning technology resources in teaching and learning of Business Education subjects in Colleges of Education in Niger State. The study adopted a descriptive survey research design. The study answered two research questions. The population for the study was 33 Business Education lecturers and 255 NCE III Business Education students from Niger State College of Education, Minna and Federal College of Education, Kontagora. No sampling was done as the population was of a manageable size, the researcher used all populations. The researcher instrument used for data collection was a structured questionnaire that contained 40 e-learning technology resources on a four-point Likert-rating scale. Mean and standard deviation were used to answer the two research questions raised for the study. The result findings revealed that e-learning technology resources are not readily available and the few available ones are not adequately utilised for the teaching of Business Education subjects in Colleges of Education in Niger State. It was concluded that lecturers need to effectively utilize the few available e-learning technology resources for the teaching and learning of Business education subjects in Colleges of Education in Niger State. It was recommended among others that Lecturers should be more motivated by governments to use the available e-learning technology resources to foster effective delivery of teaching and learning.